2019
DOI: 10.1016/j.envres.2019.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metabolites of organophosphate and pyrethroid pesticides in children from an Italian cohort (PHIME, Trieste)

Abstract: Urinary metabolites of organophosphate (OP) and pyrethroid (PYR) pesticides from seven years old children of a birth cohort study (n=199; PHIME cohort of Trieste, Italy) have been measured. Six OP and two PYR metabolites have been investigated, 2-diethylamino-6-methylpyrimidin-4-ol (DEAMPY, pirimiphos metabolite) was the one found at higher concentrations, median 3.4 ng/mL specific gravity adjusted (SG adjusted), followed by 4nitrophenol (PNP, median 1.4 ng/mL SG adjusted) and 3,5,6-trichloro-2-pyridinol (TCPY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 83 publications
0
7
1
Order By: Relevance
“…The urinary PNP metabolite can also result from exposure to environmental PNP resulting from natural environmental degradation of parathion or methyl parathion. However, considering the high reactivity of parathion and its low persistence in environmental samples, PNP concentrations probably reflect recent contributions in the studied cohort (Bravo et al 2019). After acute exposures, most of the metabolites are rapidly excreted in the urine (Abu-Qare and Abou-Donia 2000; Braeckman et al 1983), but chronic exposures to parathion and parathion-methyl, as well as with any non-persistent organic toxicant, can result in steady-state metabolite excretion.…”
Section: Reported a Higher Mean Pnp Concentrationmentioning
confidence: 98%
See 2 more Smart Citations
“…The urinary PNP metabolite can also result from exposure to environmental PNP resulting from natural environmental degradation of parathion or methyl parathion. However, considering the high reactivity of parathion and its low persistence in environmental samples, PNP concentrations probably reflect recent contributions in the studied cohort (Bravo et al 2019). After acute exposures, most of the metabolites are rapidly excreted in the urine (Abu-Qare and Abou-Donia 2000; Braeckman et al 1983), but chronic exposures to parathion and parathion-methyl, as well as with any non-persistent organic toxicant, can result in steady-state metabolite excretion.…”
Section: Reported a Higher Mean Pnp Concentrationmentioning
confidence: 98%
“…The most common PYR pesticides, including permethrin, cypermethrin, and deltamethrin, are metabolized to 3-phenoxybenzoic acid (3-PBA), while cyfluthrin is metabolized to 4-fluoro-3phenoxybenzoic acid (4-F-3-PBA). The determination of the organic metabolite moieties in the urine provides information on the internal doses of the specific parental compounds that allows assessing the exposure to individual pesticides (Barr et al 2002;Barr 2008;Koureas et al 2012;Bravo et al 2019Bravo et al , 2020a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest national standard GB 2763-2021 stipulates that the maximum residue limit of fenpropathrin in fruit is 5 mg/kg, that in cabbage iss 1 mg/kg and that in cucumber is 0.2 mg/kg. The maximum residue limit of cypermethrin in apple, pear and cabbage is 2 mg/kg, and the maximum residue limit of fenvalerate in apple, pear and cabbage is 1 mg/kg; EU standard EU441/2012 stipulates that the maximum residue of bifenthrin in tomato is 0.3 mg/kg, and the maximum residues of fenvalerate and beta cypermethrin in potato are 0.02 mg/kg and 0.01 mg/kg [ 15 , 16 , 17 ]. Even though there are limited requirements in the national standards, the excessive residue of pyrethroid pesticides in edible agricultural products has been banned repeatedly.…”
Section: Introductionmentioning
confidence: 99%
“…Several human biomonitoring studies measured urinary pyrethroids and chlorpyrifos metabolites in children populations over the world and showed that their levels vary (Wang et al, 2016;van Wendel de Joode et al, 2016;CDC, 2019;Bravo et al, 2019;Health Canada, 2019;Panuwet et al, 2009;Muñoz-Quezada et al, 2020;Fernández S et al, 2020). Indicatively, the median urinary levels of the common metabolite (3-PBA) for many pyrethroids was <LOD (8 ng/L) in 406 Chinese children aged 3-6 years in 2014 (Wang et al, 2016), 0.38 μg/L in 534 children aged 6-11 years in Canada in -2017(Health Canada, 2019 and 1.63 μg/L in 568 Spanish children aged 5-12 years in 2016 (Fernández S et al, 2020).…”
Section: Introductionmentioning
confidence: 99%